If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -1 + 3p = 3 Reorder the terms: -1 + p + 3p = 3 Combine like terms: p + 3p = 4p -1 + 4p = 3 Solving -1 + 4p = 3 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4p = 3 + 1 Combine like terms: -1 + 1 = 0 0 + 4p = 3 + 1 4p = 3 + 1 Combine like terms: 3 + 1 = 4 4p = 4 Divide each side by '4'. p = 1 Simplifying p = 1
| 6x+4+2x-2+4x-14=180 | | 2(4x-5)=54 | | Y=2400+250x | | -8n-3n=66 | | 3m-6n=18 | | lx-4l=lx-8l | | 19x-34= | | x=.50*50+60 | | 7x-8w+2x+9y+5y+4w= | | 2x-8+6x=-9x+x | | 12=1+X+3 | | -37=-7x+2x-2 | | 4cosx-(2sinx)=2 | | 2x=1000-200x | | 5x+3=2x-5+3x | | -5.4z=3.4 | | 4cosx-2sinx=2 | | 5y+4(-y-4)=-11 | | 8x-(x-5)=x+25 | | -36=2v+2(v-4) | | -7X+2+X=-16 | | 16x+4=5x-6x | | 2x+2y-2y= | | 3y-y+5y-(-2y)=-108 | | 2=-4(2x-9)+6x | | 16=X+8+2 | | (0.5x-4)-(1.5x+2.3)= | | 19x-8=12x-43 | | 12(4+n)+5(-2n-9)=1 | | 5a+8-4=-21 | | 116=-4x+2(-5x-5) | | 12x^2-96x+0=0 |